GAMBARAN SISTEM ANTRIAN PASIEN DALAM OPTIMASI PELAYANAN DI LOKET PENDAFTARAN INSTALASI RAWAT JALAN RUMAH SAKIT UMUM PUSAT FATMAWATI - Ade Selvia Septiani; Putri Asmita Wigati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Queue is a situation where there are customers who have to wait to get service. This queuing process also occurs in the outpatient registration service of RSUP Fatmawati. The number of patient visits in the outpatient installation within a year in 2016 is 329.622 patients. The queue will occur if the existing facilities have not been able to keep up the patient’s arrival rate. The purpose in this study is to describe the system of patient queues for service optimization at registration counter in outpatient installation of RSUP Fatmawati. The method used in this study is quantitative method with descriptive survey and cross sectional approach. Data collecting was done by doing a calculation of arrival rate and service rate at the registration counter of 4 polyclinics, with accidental sampling method. The results showed that the outpatient service flow in RSUP Fatmawati started with taking the queue number and waiting for a call at registration counter. The sample in June showed that the highest arrival rate was the counter of other polyclinic as many as 90 patients/hour; and the highest service rate was the counter of obstetric polyclinic as many as 32 patients/hour. The sample in July showed that the highest arrival rate was the counter of other polyclinic as many as 94 patients/hour; and the highest service rate was surgical polyclinic counters as many as 39 patients/hour. Based on the result in this study, only the surgical polyclinic counters have reached the optimal point of the system where patient waiting times are shorter and the server’s idle time is less than the others. The additional number of counters is recommended for obstetric polyclinic counter and pulmonary polyclinic counter to reduce patient waiting time. Reoperation of 2 other counters at the counters of other polyclinic is also recommended to reduce the high workload of the existing servers.